Adenovirus infection in savanna chimpanzees (Pan troglodytes schweinfurthii) in the Issa Valley, Tanzania - Dadáková, Eva; Brožová, Kristýna; Piel, Alex K; Stewart, Fiona A; Modrý, David; Celer, Vladimír; Hrazdilová, Kristýna (Archives of virology, 2018)
Adenoviruses are a widespread cause of diverse human infections with recently confirmed zoonotic roots in African great apes. We focused on savanna-dwelling chimpanzees in the Issa Valley (Tanzania), which differ from those from forested sites in many aspects of behavior and ecology. PCR targeting the DNA polymerase gene detected AdV in 36.7% (69/188) of fecal samples. We detected five groups of strains belonging to the species Human mastadenovirus E and two distinct groups within the species Human mastadenovirus C based on partial hexon sequence. All detected AdVs from the Issa Valley are related to those from nearby Mahale and Gombe National Parks, suggesting chimpanzee movements and pathogen transmission.
Keywords: DNA-Directed DNA Polymerase; Animals; Ape Diseases; Adenoviridae Infections; Adenoviridae; Phylogeny; zvířata; DNA-dependentní DNA-polymerasy; feces; Feces; fylogeneze; Tanzania; adenovirové infekce; Pan troglodytes; Tanzanie; nemoci lidoopů